Pembiasaan Membaca Asmaul Husna Pagi Hari Dalam Penguatan Karakter Religius Siswa - Ashabil Sanjaya; Salman Iymaanullah; Agum Pirmansah; Faridah Husna; Rani Rani; Muhamad Ibnu Malik (GLOBAL SCIENTS PUBLISHER, 2026)
The habituation of reading Asmaul Husna has become an increasingly recognized strategy for strengthening the religious character of elementary school students amidst the challenges of moral degradation in the digital era. This study aims to analyze the implementation and impact of Asmaul Husna reading habituation on the reinforcement of students' religious character in elementary schools. This research employs a systematic literature review method by examining 30 empirical studies published between 2020 and 2026, sourced from accredited national and international journals. The findings reveal that the habituation of reading Asmaul Husna is implemented through various structured activities, including daily routines before learning, integration into Islamic Religious Education (PAI) lessons, and extracurricular religious programs. This habituation significantly contributes to the development of religious character indicators such as discipline, responsibility, honesty, tolerance, and piety. The study also identifies supporting factors, including teacher role modeling, parental involvement, and a conducive school environment, as well as inhibiting factors such as students' diverse backgrounds and limited facilities. The results affirm that Asmaul Husna reading habituation is an effective pedagogical strategy for fostering students' religious character from an early age.